Epidemiology of Burkholderia pseudomallei, Streptococcus suis, Salmonella spp., Shigella spp. and Vibrio spp. infections in 111 hospitals in Thailand, 2022. - Charuttaporn Jitpeera; Somkid Kripattanapong; Preeyarach Klaytong; Chalida Rangsiwutisak; Prapass Wannapinij; Pawinee Doungngern; Papassorn Pinyopornpanish; Panida Chamawan; Voranadda Srisuphan; Krittiya Tuamsuwan; Phairam Boonyarit; Orapan Sripichai; et al. (PLOS Global Public Health)
The information on notifiable diseases in low- and middle-income countries is often incomplete, limiting our understanding of their epidemiology. Our study addresses this knowledge gap by analyzing microbiology laboratory and hospital admission data from 111 of 127 public referral hospitals in Thailand, excluding Bangkok, from January to December 2022. We evaluated factors associated with the incidence of notifiable bacterial diseases (NBDs) caused by 11 pathogens; including Brucella spp., Burkholderia pseudomallei, Corynebacterium diphtheriae, Neisseria gonorrhoeae, Neisseria meningitidis, non-typhoidal Salmonella spp. (NTS), Salmonella enterica serovar Paratyphi, Salmonella enterica serovar Typhi, Shigella spp., Streptococcus suis, and Vibrio spp.. We used multivariable Poisson random-effects regression models. Additionally, we compared their yearly incidence rates in 2022 with those from 2012-2015 in hospitals where paired data were available. In 2022, the NBD associated with the highest total number of deaths was B. pseudomallei (4,407 patients; 1,219 deaths) infection, followed by NTS (4,501 patients; 461 deaths), S. suis (867 patients, 134 deaths) and Vibrio spp. (809 patients, 122 deaths) infection. The incidence rates of B. pseudomallei, S. suis and Vibrio spp. infections were highest in the northeast, upper central and west, respectively. The incidence rate of NTS infection was generally high across all geographical regions. The yearly incidence rates of B. pseudomallei and S. suis infections in 2022 were higher than those between 2012-2015, while those of fecal-oral transmitted NBDs including NTS infection, typhoid, shigellosis and vibriosis were lower. Overall, B. pseudomallei and S. suis infections are emerging and associated with a very high number of deaths in Thailand. Although the incidence of NTS infection and vibriosis are decreasing, they are still associated with a high number of cases and deaths. Specific public health interventions are warranted.